A PVDF electrospun antifibrotic composite for use as a glaucoma drainage implant - Klapstova, Andrea; Horakova, Jana; Tunak, Maros; Shynkarenko, Andrii; Erben, Jakub; Hlavata, Jana; Bulir, Petr; Chvojka, Jiri (Materials science & engineering. C, Materials for biological applications, 2021)
Glaucoma disease therapy frequently involves the application of a glaucoma implant. This approach is effective in terms of reducing the intraocular pressure via the filtering of intraocular fluid from the anterior chamber into the drainage pathways. The basic properties of such implants comprise of long-term stability and the filtering of fluids without the occurrence of undesirable blockages. This study describes the design and production of a novel material for the treatment of glaucoma disease that is based on electrospinning technology. Non-toxic, biocompatible and non-degradable polyvinylidenefluoride (PVDF) was selected as the implant material. The research investigated the resistance of this material to the growth of a fibroblast cell line without the use of antifibrotic agents such as mitomycin C. Three different types of PVDF were electrospun separately and mixed with polyethyleneoxide (PEO), following which the degree of cell growth resistance was evaluated. It was discovered that the fiber layers that contained PVDF blended with PEO evinced a statistically significant difference in metabolic activity compared to the PURE PVDF layers. Only small cell clusters formed on the layers that were resistant to cell fibrotization. As a result of the observed clustering, a new program was developed in MATLAB software for the determination of the number of cells involved in cluster formation, which then allowed for the determination of the spatial dependence between the cells in the form of a point pattern. The study describes a simple technique for the production of composite PVDF+PEO structures suitable for use in the field of glaucoma treatment.
Keywords: Intraocular Pressure; Electrospinning; Glaucoma Drainage Implants; nitrooční tlak; Glaucoma drainage implant; Nanofibers; glaukom; Polyvinylidenefluoride; Aqueous Humor; komorová voda; Humans; mitomycin; Mitomycin; Ophthalmology; Composite materials; drenážní implantáty glaukomové; Glaucoma; lidé